HOW IS THE IMPACT OF INSTRUCTIONAL LEARNING USING AN ETHNOSCIENCE APPROACH?; ANALYSIS OF THE CONTRIBUTION OF STUDENTS' CREATIVE THINKING SKILLS - Khoiri, Ahmad; Saputro, Budiyono; Agussuryani, Qori; Miterianifa, Miterianifa; Trisnayanti, Yetty (Program Studi Pendidikan Fisika, FITK, UNSIQ, 2024)
The instructional impact of learning using an ethnoscience approach is often ignored, even though its contribution to students' creative thinking skills is very much needed. The research aims to analyze the direct contribution to students' creative thinking skills. Quasi-experimental research method with pre-test post-test control group design. Data collection used a standardized TTCT (Torrance Test Creative Thinking) question instrument. The analysis technique uses the MANOVA F test. The results show that learning with an ethnoscience approach can contribute to student's creative thinking skills based on the MANOVA f test that all components are significant (Sig. < 0.05). Learning with an ethnoscience approach significantly influences each indicator of Fluency, Flexibility, Originality, Elaboration, and Redefinition with a P-Value of 0.000. The largest contribution is the R-squared value of 0.568 for the experimental class and 0.561 for the control class in the Originality indicator. The coefficient of determination is based on the R2 value (0.568)2: 0.32 x 100%: 32% of learning using an ethnoscience approach to creative thinking skills. Students' ability to develop original thinking has more dominant results compared to other indicators of creative thinking skills. Recommendations for the importance of learning design that considers students' learning needs and cultural backgrounds. The ethnoscience approach can provide students with opportunities to think contextually in solving problems so that creative thinking skills are easier to improve.